Case Study in the Indonesian Banking Sector: Implementation of the Policy on The Use of Collateral in the People's Business Credit Kur in The Coordinating Minister of Economic Regulation Number 7 of 2024 - Mulyono, Guruh Sugeng; Saktiawan, Pratolo; Mujito, Mujito (Dinasti Publisher, 2025)
This research aims to be a Case Study in the Indonesian Banking Sector: Implementation of the Policy for Using KUR People's Business Credit Collateral in Permenko Perekonomian Nomor 7 Tahun 2024 . The research background arises from the need to understand the implementation and impact in practice of credit protection policies in the banking sector. These findings provide insight for practitioners, academics and regulators regarding the implementation of the Collateral Use Permenko Perekonomian Nomor 7 Tahun 2024 Policy of Coordinating Minister for the Economy Number 7 of 2024 concerning People's Business Credit.